Antinéa - Demetre H. Chiparus - Maulhardt, Astrid (Colección de Arte Amalia Lacroze de Fortabat, 2019)
Analitical texts on Art-Deco sculpture "Antinea", a cold painted bronze and ivory figure of an Egyptian dancer (circa 1928) by Demétre Haralamb Chiparus (Romania 1886 - Paris, France 1947), one of the most eminent and recognisable sculptors of the the European Art Deco period
Keywords: Chiparus, Demetre -- 1886-1947; Plastik; Art Déco; Chiparus, Demetre / 1886- / Antinéa; Art deco / France; Figure sculpture / France; Art deco; France; Criticism, interpretation, etc